Peran Negara Dalam Hubungan Tenaga Kerja di Indonesia - Subijanto -- (Jurnal Pendidikan dan Kebudayaan, 2011)
The aim of this writing article is to identify the function of the Indonesian Government in relation with Indonesian labor force and the relation of labor force organization. Until now, the foundamental problem of the Indonesian job seekers is lack of functional basic skill. Globalization era, has requirement for every job seekers to have competence and to be able to competitive in certain job qualification requirement. Based on the legal formal, the Indonesian labourforce has been protecting by a number of laws, namely: 1) the amandement of the 1945 Constitutionof the Republic of Indonesia (article,27 sub article (2) stated that every citizen shall have the right job and welfare for human being; 2) the act number 39, year 1999 about Human Right an article 38 sub article 1 stated that every citizen, according to potential talent, skill, and smart, shal have the right job. Furthermore, subarticle 2 stated that every people shall have the freedom of choice according to interest and requirement accordingly. Subarticle 3 stated that every people, event women or man to be equal in doing job according to the status of bwckground to get wage in order to be sustainable life; and 3) the act number 13, year 2003 about labour force. In relation with preparation of job seekers the Ministry of National Education (MoNE) has obligation to improve the quality of education and relevance with outcome of education.Meanwhile, the Ministry of Manpower and Transmigration has responsible anda specific task to do the competence of certification through National Board of Proffesional Standard (BNSP) and Institution of Proffesional Standar (LSP).